La bande dessinée contemporaine au rendez-vous de la mémoire violente de l’après-guerre civile espagnole et du premier franquisme - Viviane Alary (Cahiers de Civilisation Espagnole Contemporaine)
Many comic book authors have chosen to tell the story of individual destinies by interweaving them into a collective history, that of Spain under Franco's regime. This article sheds light on the work of memory that Spanish comics have been undertaking since the 1970s through four graphic works placed in the context of their first publication (the Paracuellos series, 1977; El artefacto perverso, 1996; Cuerda de presas, 2005; Los surcos del azar, 2013). It analyzes the narrative and graphic choices as well as the formats and genres in which this memory of Franco's regime, based on testimony, investigation and consideration of historiographical advances, is embodied. The modalities specific to each author facilitate the reader's access to certain historical knowledge transformed into autofiction, detective fiction, fictionalized testimony, graphic journalism.